Pragmatic versus structural difficulties in the production of pronominal clitics in French-speaking children with autism spectrum disorder. (September 2018) - Prévost, Philippe; Tuller, Laurice; Zebib, Racha; Barthez, Marie Anne; Malvy, Joëlle; Bonnet-Brilhault, Frédérique
Background and aims: Impaired production of third person accusative pronominal clitics is a signature of language impairment in French-speaking children. It has been found to be a prominent and persistent difficulty in children and adolescents with specific language impairment. Previous studies have reported that many children with autism spectrum disorder also have low performance on these clitics. However, it remains unclear whether these difficulties in children with autism spectrum disorder are due to structural language impairment or to pragmatic deficits. This is because pragmatics skills, notoriously weak in children with autism spectrum disorder, are also needed for appropriate use of pronouns. Use of pronouns without clear referents and difficulty with discourse pronouns (first and second person), which require taking into account the point of view of one's interlocutor (perspective shifting), have frequently been reported for autism spectrum disorder. Methods: We elicited production of nominative, reflexive and accusative third and first person pronominal clitics in 19 verbal children with autism spectrum disorder (aged 6–12, high and low functioning, with structural language impairment, or with normal language) and 19 age-matched children with specific language impairment. If pragmatics is behind difficulties on these elements, performance on first-person clitics would be expected to be worse than performance on third person clitics, since it requires perspective shifting. Furthermore, worse performance for first person clitics was expected in the children with autism spectrum disorder compared to the children with specific language impairment, since weak pragmatics is an integral part of impairment in the former, but not in the latter. More generally, different error patterns would be expected in the two groups, if the source of difficulty with clitics is different (a pragmatic deficit vs. a structural language deficit). Results: Similar patterns of relative difficulties were found in the autism spectrum disorder language impairment and specific language impairment groups, with third person accusative clitics being produced at lower rates than first-person pronouns and error patterns being essentially identical. First-person pronouns did not pose particular difficulties in the children with autism spectrum disorder (language impairment or normal language) with respect to third-person pronouns or to the children with specific language impairment. Performance was not related to nonverbal intelligence in the autism spectrum disorder group. Conclusions: The elicitation task used in this study included explicit instruction, and focus on perspective shifting (both visual and verbal), allowing for potential pragmatic effects to be controlled. Moreover, the task elicited a variety of types of clitics in morphosyntactic contexts of varying complexity, providing ample opportunities for employment of perspective shifting, which may have also curtailed perseveration of third person over first person. These properties of the task allowed for the grammatical nature of children's difficulties with third-person accusative clitics to emerge unambiguously. Implications: Assessment of structural language abilities in children with autism spectrum disorder requires careful consideration of task demands. The influence of pragmatic abilities on structural language performance can be circumvented by making the pragmatic demands of the task explicit and salient. Filtering out this potential influence on structural language performance is fundamental to understanding language profiles in children with autism spectrum disorder and thus which children could benefit from which kinds of language intervention.